Unraveling the spatial distribution and influencing factors of 'Bengke' traditional houses in Luhuo County, Western Sichuan. - Siwei Yu; Ding Fan; Ma Ge; Zihang Chen (PLoS ONE)
The article examines the spatial distribution characteristics and influencing factors of traditional Tibetan "Bengke" residential architecture in Luhuo County, Ganzi Tibetan Autonomous Prefecture, Sichuan Province. The study utilizes spatial statistical methods, including Average Nearest Neighbor Analysis, Getis-Ord Gi*, and Kernel Density Estimation, to identify significant clustering patterns of Bengke architecture. Spatial autocorrelation was tested using Moran's Index, with results indicating no significant spatial autocorrelation, suggesting that the distribution mechanisms are complex and influenced by multiple factors. Additionally, exploratory data analysis (EDA), the Analytic Hierarchy Process (AHP), and regression methods such as Lasso and Elastic Net were used to identify and validate key factors influencing the distribution of these buildings. The analysis reveals that road density, population density, economic development quality, and industrial structure are the most significant factors. The study also highlights that these factors vary in impact between high-density and low-density areas, depending on the regional environment. These findings offer a comprehensive understanding of the spatial patterns of Bengke architecture and provide valuable insights for the preservation and sustainable development of this cultural heritage.